2016
DOI: 10.1016/j.cell.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Insulated Neighborhoods: Structural and Functional Units of Mammalian Gene Control

Abstract: Summary Understanding how transcriptional enhancers control over 20,000 protein-coding genes to maintain cell type-specific gene expression programs in all human cells is a fundamental challenge in regulatory biology. Recent studies suggest that gene regulatory elements and their target genes generally occur within insulated neighborhoods, which are chromosomal loop structures formed by the interaction of two DNA sites bound by the CTCF protein and occupied by the cohesin complex. We review here evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
371
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(381 citation statements)
references
References 104 publications
(191 reference statements)
8
371
0
2
Order By: Relevance
“…Although enhancers can activate any gene, they are physically and functionally constrained to act within insulated neighborhoods (Figure 2D) (Hnisz et al, 2016a). Insulated neighborhoods are chromosomal loop structures formed by the interaction of two DNA sites bound by the CTCF protein and occupied by the cohesin complex.…”
Section: Transcriptional Programs In Normal Cellsmentioning
confidence: 99%
“…Although enhancers can activate any gene, they are physically and functionally constrained to act within insulated neighborhoods (Figure 2D) (Hnisz et al, 2016a). Insulated neighborhoods are chromosomal loop structures formed by the interaction of two DNA sites bound by the CTCF protein and occupied by the cohesin complex.…”
Section: Transcriptional Programs In Normal Cellsmentioning
confidence: 99%
“…These technologies provided critical insights into key structural and functional components of three-dimensional chromatin organization such as i) A/B compartments (Lieberman-aiden et al 2009), also referred to as compartment domains (Rao et al 2017), which are closely associated with open and closed chromatin domains, respectively; ii) topologically associating domains (TADs) (Dixon et al 2012;Nora et al 2012;Sexton et al 2012), also referred to as contact domains (Rao et al 2017), chromosomal units that spatially constrain cis-regulatory interactions; iii) CTCF loops, also referred to as insulated neighborhoods (Hnisz et al 2016) or loop domains (Rao et al 2017). Interestingly, while these studies suggested a hierarchical domain organization, recent studies based on acute depletion of CTCF or cohesin, or inactivation of the cohesin-loading factor NIPBL, demonstrated that A/B compartments and TADs are not hierarchically organized but represent independent structural (and possibly functional) units of 3D genome organization (Nora et al 2017;Rao et al 2017;Wutz et al 2017;Schwarzer et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Different subgroups of transcribed Hoxd genes are bordered by bound CTCF and cohesin TAD borders are often enriched in both CpG islands and sites bound by architectural proteins, which may be instrumental in either their formation or their maintenance (Guelen et al 2008;Dixon et al 2012). For instance, CTCF and the cohesin complex can form loops between distant regions and hence favor the segregation of chromatin interaction patterns (see Phillips-Cremins et al 2013;Hnisz et al 2016). The HoxD cluster displays a dense distribution of at least 21 identified CpG islands and contains >10 different promoters, including coding and noncoding genes ( Fig.…”
Section: A Tad Border Within the Hoxd Clustermentioning
confidence: 99%